1997
DOI: 10.1073/pnas.94.1.73
|View full text |Cite
|
Sign up to set email alerts
|

A computer screening approach to immunoglobulin superfamily structures and interactions: Discovery of small non-peptidic CD4 inhibitors as novel immunotherapeutics

Abstract: The interaction between CD4 and major histocompatibility complex (MHC) class II proteins is critical for the activation of CD4 ؉ T cells, which are involved in transplantation reactions and a number of autoimmune diseases. In this study we have identified a CD4 surface pocket as a functional epitope implicated in CD4-MHC class II interaction and T-cell activation. A computer-based strategy has been used to screen Ϸ150,000 non-peptidic organic compounds in a molecular data base and to identify a group of compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 42 publications
1
42
0
1
Order By: Relevance
“…This raised the possibility that the weak monomeric CD4-MHC affinity could be overcome by augmenting the avidity of the interaction through CD4 dimerization/oligomerization. Several crystallographic, molecular modeling, biochemical, and functional studies have indicated the involvement of CD4 oligomers in MHC class II binding and/or T cell activation (12,(17)(18)(19)(20)(21)(22). Confirming the crystallographic data, we identified K318 and Q344, two highly conserved residues within the D4 domain, as critical for CD4 dimer formation, assessed biochemically.…”
Section: T He Adaptive Immune Response Is Activated When Tcrs On the supporting
confidence: 57%
“…This raised the possibility that the weak monomeric CD4-MHC affinity could be overcome by augmenting the avidity of the interaction through CD4 dimerization/oligomerization. Several crystallographic, molecular modeling, biochemical, and functional studies have indicated the involvement of CD4 oligomers in MHC class II binding and/or T cell activation (12,(17)(18)(19)(20)(21)(22). Confirming the crystallographic data, we identified K318 and Q344, two highly conserved residues within the D4 domain, as critical for CD4 dimer formation, assessed biochemically.…”
Section: T He Adaptive Immune Response Is Activated When Tcrs On the supporting
confidence: 57%
“…The involvement of CD4 oligomers in MHC class II binding and/or T cell activation has been previously suggested, but not proven, by a panoply of crystallographic studies (13,37), molecular modeling studies (reviewed in Ref. 10), functional studies (11,15,24,38), and inhibition of IL-2 production using synthetic peptides (39,40). In addition, CD4 oligomerization has been reported to be critical for an efficient interaction of CD4 with other ligands, such as gp160 or IL-16 (6 -10, 41).…”
Section: Discussionmentioning
confidence: 99%
“…Virtual (also called in silico) screening of chemical libraries based on the structure of protein-protein interaction sites, ligand-receptor interaction sites, or a series of known small ligands is a potentially powerful approach for the identification of novel lead compounds (for review, see Kurogi and Guner, 2001;Mason et al, 2001;Guner, 2002;Singh et al, 2002;Guner et al, 2004). To date, in the area of modulation of protein-protein interactions, virtual screening has yielded only inhibitors, including compounds inhibiting the interactions of Bak with Bcl-2 (J. L. , Bak with Bcl-x (Enyedy et al, 2001), major histocompatibility complex class II proteins with CD4 (Li et al, 1997), and very late antigen-4 with vascular cell adhesion molecule-1 (Singh et al, 2002). As in the present work, each of these screening studies was predicated on identification of an oligopeptide with the desired function.…”
Section: Discussionmentioning
confidence: 99%